Attendance Management System / Goh Sze Eng - Goh, Sze Eng (2001)
Attendance Management System (AMS) is developed to automate entire workflow of the attendance logging system of Faculty of Computer Science and Information Technology. This system is currently in used by all the staffs in faculty. The main purpose of this project is to enhance the current system and add new functionalities to the system. The lacking of the system and all the problems faced by users will be identified in the review of literature. With the findings and the gathered information, all the functions in the system will be consolidated and the feasibility of each module will be tested. Calendar system is the new features that will be added to the system so as other new functionalities for the advantage and convenient of users. Under this project, the current database will be examined to reduce the redundancy of data and to improve its performance in term of storage and processing. Some of the tables will be normalized and the relationship between these tables will be refined too. New scheduled jobs are created to meet the needs and requirements of users as well as faculty. The interface of the system is designed and changed to be more consistent and user-friendly. Other than that, this project will also focus on the enhancement of integration with Leave Management System. The integration is carried out step by step from the development phase to implementation phase till the testing phase. Thus, the existing system will be the basis from which the better system will be developed. By making modification and adding new functionalities to the existing system, it is hoped to make the entire process of attendance faster, precise and flawless. Finally, the completion of this system will surely bring a lot of benefits to the faculty.